PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 147 PEKANBARU - Hambali, Muhammad; Marhadi, Hendri; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning science study class V SD Negeri 147 Pekanbaru. KKM achieved by school was 75. From 32 students who achieve KKM just 14 students (43.75%) while students who did’nt achieve KKM is 18 students (56.25%) with a class average of 72.15. The purpose of this research to improve outcomes IPS class V SD Negeri 147 Pekanbaru with the application of learning models Quantum Teaching. The results obtained by the average value of 72.15 basic score increased in the first cycle of 3,30% to 74.53. In the second cycle the average value of students also increased by 10,66% to 79.84. On the basic of classical completeness score IPS student learning outcomes is only 43,75% (not finished). After the professor of applied model Quantum Teaching in the first cycle classical completeness increased to 56,25% (not finished), and the second cycle of classical completeness obtained are increased to increase to 78,12%. Activities of teachers at the first meeting of first cycle acquire a percentage of 70% with good categories. The second meeting increased to 79% in good categories. In the first meeting of second cycle increased to 84% with very good category. At the second meeting increased to 90% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 68% with good categories. The second meeting increased to 77% in good categories. In the first meeting of the second cycle increased to 81% with very good category. At the second meeting increased to 86% with very good category.Keywords : Quantum Teaching, learning outcomes IPS